2011
DOI: 10.1177/0310057x1103900539
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks Associated with the R100 High Frequency Oscillatory Ventilator for Patients with Severe Hypoxaemic Respiratory Failure

Abstract: High frequency oscillatory ventilation has been shown to improve oxygenation of patients with severe respiratory failure. This prospective study examined the potential benefits and risks of the latest generation high frequency oscillatory ventilator (R100, Metran, Saitama, Japan), initiated when the target oxygenation could not be achieved by conventional mechanical ventilation in adult patients with severe hypoxaemic respiratory failure. Thirty-six patients with severe respiratory failure treated with the R10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is associated with various side effects, including injury to the airways and lung parenchyma due to its invasive nature (9). These side effects led to the invention of modern mechanical ventilation methods including high frequency oscillatory ventilation (HFOV), which can be set to trigger or to coincide with the baby's inspiratory efforts (10,11). Recent studies have confirmed the efficacy of modern ventilators as compared to conventional ventilators (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with various side effects, including injury to the airways and lung parenchyma due to its invasive nature (9). These side effects led to the invention of modern mechanical ventilation methods including high frequency oscillatory ventilation (HFOV), which can be set to trigger or to coincide with the baby's inspiratory efforts (10,11). Recent studies have confirmed the efficacy of modern ventilators as compared to conventional ventilators (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency oscillatory ventilation (HFOV) is a non-CMV technique that could improve alveolar recruitment and achieve protective ventilation with the most severe cases of ARDS using very low tidal volume (VT) and relatively high mean airway pressure (mPaw) as a surrogate for positive end-expiratory pressure (PEEP). Previous studies have clearly shown an improvement in oxygenation with HFOV [ 2 ] and even suggest a reduction in mortality [ 3 , 4 ] although the level of improvement in oxygenation is unpredictable and HFOV can indeed worsen oxygenation in some patients [ 5 ]. Alveolar recruitment—and thus improvement in gas exchange—seems to depend on the level of mPaw [ 6 , 7 ] and a high mPaw (around 30 cm H 2 O) for a period of several days seems to give the best results [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early case series of HFOV in adults reported improvements in oxygenation with variable effects on hemodynamics ( Fort et al, 1997 ; Claridge et al, 1999 ; Mehta et al, 2001 ). Subsequent studies confirmed these results, but most enrolled less than 50 subjects ( Fort et al, 1997 ; Claridge et al, 1999 ; Mehta et al, 2001 ; Andersen et al, 2002 ; David et al, 2003 ; Mehta et al, 2004 ; Ferguson et al, 2005 ; Finkielman et al, 2006 ; Pachl et al, 2006 ; Fessler et al, 2008 ; Kao et al, 2011 ; Niwa et al, 2011 ; Camporota et al, 2013 ; Jog et al, 2013 ; Naorungroj et al, 2015 ; Thind et al, 2021 ). HFOV has also been described in three small case series of burn patients involving 6 to 30 subjects with mortality between 32 and 83% ( Cartotto et al, 2001 ; Cartotto et al, 2004 ; Cartotto et al, 2009 ).…”
Section: Introductionmentioning
confidence: 97%